We solve a second order differential equation of the type:
ay''+by'+cy=f(x)
where a=1
b=3
c=2
f(x)=1/(1+e^x)
The solution will consist of common and particular solutions and have a type:
ygen=ycom+ypart
To find a common solution we solve second order differential equation y''+3y'+2y=0 and find roots of polynomial r2+3r+2=0
Its roots
"r_1={{-3+\\sqrt{3^2-4\\sdot1\\sdot2}}\\over{2\\sdot1}}={{{-3+\\sqrt{1}}\\over{2}}={{-3+1}\\over{2}}}={-1}"
"r_2={{-3-\\sqrt{3^2-4\\sdot1\\sdot2}}\\over{2\\sdot1}}={{{-3-\\sqrt{1}}\\over{2}}={{-3-1}\\over{2}}}={-2}"
Roots are complex therefore the common solution will be "y_{com}=C_1e^{-{x}}+C_2e^{-2{x}}"
We will use the method of variation of parameters to find a particular solution
"\\begin{cases}\nC'_1(x)y_1+C'_2(x)y_2=0 \\\\\nC'_1(x)y'_1+C'_2(x)y'_2={f(x)\\over {a_0}}\n\\end{cases}"
"y_1=e^{-{x}}\\\\\ny_2=e^{-{2x}}\\\\\na_0=1"
finally we get
"\\begin{cases}\nC'_1(x)e^{-{x}}+C'_2(x)e^{-{2x}}=0 (1)\\\\\n-C'_1(x)e^{-{x}}-2C'_2(x)e^{-{2x}}={1\\over {1+e^{{x}}}} (2)\n\\end{cases}"
add (2) to (1) and we get
"-2C'_2(x)e^{-{2x}}={1\\over {1+e^{x}}}\\\\\nC'_2(x)=-{e^{2x}\\over {1+e^{x}}}"
We will make some changes and simplifications
"C'_2(x)=-{e^{2x}+e^{x}-e^{x}\\over {1+e^{x}}}=-{e^{x}(e^{x}+1)\\over {e^{x}+1}}+{e^{x}\\over {e^{x}+1}}=-e^{x}+{e^{x}\\over {e^{x}+1}}"
Let us integrate C'2
"C_2(x)=\\lmoustache{(-e^{x}+{e^{x}\\over {e^{x}+1}})dx}=-e^{x}+ln\\vert{{e^{x}+1}}\\vert+C_2"
we multiply (1) by 2, add to (2) and get
"C'_1(x)e^{-{x}}={1\\over {1+e^{x}}}\\\\\nC'_1(x)={e^{x}\\over {1+e^{x}}}"
Let us integrate C'1
"C_1(x)=\\lmoustache{({e^{x}\\over {e^{x}+1}})dx}=ln\\vert{{e^{x}+1}}\\vert+C_1"
Now we add these values in our general solution for y and will get
"y_{gen}=(-e^{x}+ln\\vert{{e^{x}+1}}\\vert+C_1)e^{-{x}}+e^{-{2x}}(ln\\vert{{e^{x}+1}}\\vert+C_2)"
Finally we get
"y_{gen}=1+e^{-{x}}ln\\vert{{e^{x}+1}}\\vert+C_1e^{-{x}}+e^{-{2x}}ln\\vert{{e^{x}+1}}\\vert+C_2e^{-{2x}}"
Comments
Leave a comment